PENGARUH MANAJEMEN PERKANTORAN TERHADAP EFEKTIVITAS KERJA PADA KANTOR KECAMATAN SUNGAI PINANG KOTA SAMARINDA - Mirza Ahmad (ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine the Effect of Office Management on Work Effectiveness at the Sungai Pinang District Office, Samarinda City. The results showed that Office Management has a positive effect on Work Effectiveness at the Sungai Pinang District Office, Samarinda City. The result of the Person Product Moment correlation between X and Y is r = 0.694.So there is an influence between Office Management on Employee Work Effectiveness at the Sungai Pinang District Office, Samarinda City of 0.694.The result of the t-test is 5,534. This means that it can also be said that thit = 5,534, this result when compared with the value in the table of critical prices, t-student is bigger, namely thit = 5,534> ttab = 2,034, this shows that there is a positive influence of office management variables on work effectiveness variable at the Sungai Pinang District Office, Samarinda City